Location aware system using bluetooth low energy beacons - Law, Chin Hao (2014)
Bluetooth Low Energy (BLE) is a wireless technology with low power consumption that can be used by newer Bluetooth devices. This research focuses on implementing a way to deliver location based information from a content management system (CMS) to a mobile application by using location detection. The location detection feature of the mobile application uses beacon devices that run under BLE for positioning. By adding location awareness feature into a mobile application, mobile users can quickly find information relevant to their current position.